Inhibition SIRT1 to regulate FOXP3 or RORγt can restore the balance of Treg/Th17 axis in ulcerative colitis and enhance the anti-inflammatory effect of moxibustion - Zhu, Yuanbing; Wang, Yuemei; Zuo, Xiaotong; Liu, Shuqing; Cao, Lishuang; Wang, Junmeng; Yang, Qingqing; Huang, Qianhui; Huang, Qin; Tian, Muqiu; Ping, Yanling; Wu, Qiaofeng (Frontiers in Immunology, 2025)
IntroductionUlcerative colitis (UC) is a chronic inflammatory disease. Patients with UC typically exhibit disruption of the Treg/Th17 immune axis, but its exact mechanism is still unclear.MethodsThis study first analyzed RNA- seq data from public databases of humans and mice, and in vitro cytology experiments were conducted to induce or inhibit the expression of SIRT1. In vivo, UC mice were treated with moxibustion and SIRT1 inhibitor EX-527 to confirm the changes in the transcription factors identified through analysis of the datasets.ResultsThe results show that Treg/Th17 axis disruption is an important feature of UC. Differential gene expression and immune infiltration analysis showed that upstream transcription factors, including Forkhead box P3 (FOXP3), were significantly disrupted. In vitro cytology experiments, the results indicate that SIRT1 is activated in LPS induced inflammation, subsequently perturbing the Treg/Th17 immune balance axis. Finally, in vivo studies, the results have shown that administering EX-527 to inhibit SIRT1 leads to an increasing in FOXP3 expression and a decreasing in RORγt expression in UC colon tissue. In addition, the results indicate that traditional Chinese moxibustion can down regulate the expression of SIRT1, directly affecting the balance of Th17/Treg axis, and the combined use of EX-527 further improves the therapeutic effect of moxibustion.ConclusionOur research shows that inhibition SIRT1 can regulate Treg and Th17 immune balance axis. This finding indicates a new important potential target for the treatment of UC.